Motor speech disorders : substrates, differential diagnosis, and management - Duffy, Joseph R. (St. Louis, Missouri : Elsevier, 2020)
'Motor Speech Disorders integrates the latest neurological research with the realities of clinical practice. The fourth edition is divided into three sections which focus on substrates of motor speech and its disorders, the disorders and their diagnoses, and finally managing various treatment types. Additionally, new research on the neurologic organization of motor control, causes of motor speech disorders, and advances in the medical and behavioral management of specific disorders is incorporated throughout.'--Publisher website: https://www.elsevier.com/books/motor-speech-disorders/duffy/978-0-323-53054-5
Part 1: Substrates: Defining, understanding, and categorizing motor speech disorders -- Neurologic bases of motor speech and its disorders -- Examination of motor speech disorders -- Part 2: Disorders and their diagnoses: Flaccid dysarthrias -- Spastic dysarthria -- Ataxic dysarthria -- Hypokinetic dysarthria -- Hyperkinetic dysarthrias -- Unilateral upper motor neuron dysarthria -- Mixed dysarthrias -- Apraxia of speech -- Neurogenic mutism -- Other neurogenic speech disturbances -- Functional (psychogenic) and related speech disorders -- Differential diagnosis -- Part 3: Management: Managing motor speech disorders: Broad overview -- Managing the dysarthias -- Managing apraxia of speech -- Managing other neurogenic speech disturbances -- Managing functional (psychogenic) speech disorders.
'Evolve learning resources for students and lecturers.'
Includes bibliographical references and index.
Online access password : MRJGJPPYKR53
Online access password : MRMTBYX9P6HJ (not register yet). (PPUKM).
Keywords: Dysarthria -- diagnosis; Dysarthria -- therapy; Speech Disorders -- diagnosis; Speech Disorders -- therapy